Atmospheric science for environmental scientists - Hewitt, C. N.; Jackson, Andrea V.
"The causes, history and distributions of the Earth's climates are introduced in this chapter. The combination of the distribution of incoming solar radiation across the Earth's surface and the Earth's rotation, drive and shape the observed atmosphere-ocean circulation. Important factors, which determine changes in climate, include palaeo-geography, greenhouse gas concentrations, changing orbital parameters, and varying ocean heat transport. One of the major controls of climatic changes is the greenhouse gas concentration of the atmosphere, in particular that of carbon dioxide. Before the Eocene-Oligocene boundary ( 34 Myr ago) the atmosphere-ocean circulation sup-ported a warm atmosphere and ocean, with both poles free of permanent ice. At the Eocene-Oligocene boundary the atmosphere-ocean circulation changed to a form similar to the present, and the first evidence of an Antarctic ice sheet is found. Falling atmospheric carbon dioxide levels probably caused this change. The waxing and waning of massive temperate latitude continental ice sheets characterize the climate of the past million years. Recent cli-mate changes are described and evidence produced that they are largely driven by anthropogenic generated at-mospheric carbon dioxide. In particular recent climate changes are causing the expansion of the tropical zone and a retreat of the polar zones"--Provided by publisher.
AU Novero (Recommending faculty) AY 2023-2024
Includes bibliographical references and index.
Keywords: Atmospheric physics -- Textbooks; Atmospheric science; Environmental sciences -- Textbooks